Self‐Assembly and Neurotoxicity of β‐Amyloid (21–40) Peptide Fragment: The Regulatory Role of GxxxG Motifs. (3rd December 2019) - Sarkar, Dibakar; Chakraborty, Ipsita; Condorelli, Marcello; Ghosh, Baijayanti; Mass, Thorben; Weingarth, Markus; Mandal, Atin K; La Rosa, Carmelo; Subramanian, Vivekanandan; Bhunia, Anirban
Abstract: The three GxxxG repeating motifs from the C‐terminal region of β‐amyloid (Aβ) peptide play a significant role in regulating the aggregation kinetics of the peptide. Mutation of these glycine residues to leucine greatly accelerates the fibrillation process but generates a varied toxicity profile. Using an array of biophysical techniques, we demonstrated the uniqueness of the composite glycine residues in these structural repeats. We used solvent relaxation NMR spectroscopy to investigate the role played by the surrounding water molecules in determining the corresponding aggregation pathway. Notably, the conformational changes induced by Gly 33 and Gly 37 mutations result in significantly decreased toxicity in a neuronal cell line. Our results indicate that G 33 xxxG 37 is the primary motif responsible for Aβ neurotoxicity, hence providing a direct structure–function correlation. Targeting this motif, therefore, can be a promising strategy to prevent neuronal cell death associated with Alzheimer's and other related diseases, such as type II diabetes and Parkinson's. Abstract : The regulatory role of GxxxG repeating motifs from the C‐terminal region of Aβ peptide in its aggregation kinetics has been demonstrated by various biophysical studies. Mutation of these glycine residues to leucine greatly accelerates the fibrillation process, but generates a varied toxicity profile. Our results indicate that G 33 xxxG 37 is the primary motif responsible for Aβ neurotoxicity. Solvent relaxation NMR indicates the role played by the surrounding water molecules in determining the corresponding aggregation pathway.